Korean Dynasty Confucian Li Huang and Han Yuanzhen’s Contribution on Zhu Xi’s Ritual Study - Yiping, Liu (Sinología hispánica. China Studies Review, 2016)
The Confucians in the era of Korean Dynasty have inherited and developed Zhu Xi’s ritual study. Li Huang, composed Shengxue Shitu based on Jin Si Lu, aiming at pursuing prudence and morality, and putting them into practice, had great impact on the development of Confucianism in Korean Dynasty. Han Yuanzhen regarded Yili Jingzhuan Tongjie as the second ritual composition made by Confucians after Zhougong, and developed it into Yili Jingzhuan Tongjie Bu based on Zhu Xi’s way，attempting at converting the Yili Jingzhuan Tongjie into ritual classics of the era. Li Huang’s development of Zhu Xi’s ritual spirit is the localization of Confucianism and Zhu Xi’s theory. And Han Yuanzhen’s development of annotation of Zhu Xi’s theory is the Korean Dynasty Confucians’ answer to the public issues of Confucianism.